Ideological Political Contestation in the Discourse of Hisab Rukyat in Indonesia - Hefni, Wildani (Jurnal Penelitian, 2019)
This article discusses the ideological contestation of the two mass organizations, Muhammadiyah and Nahdlatul Ulama (NU), that are the spearhead of the two paradigms in determining the beginning of the month of qamariah. Hisab is initiated by Muhammadiyah and rukyat is pioneered by Nahdlatul Ulama (NU). These two paradigms are the cause of the emergence of tension conflict due to the non-uniformity of the method of determining the beginning of the qamariah month in Indonesia. By using a power relations approach and reading of religious commodification, this article concludes that fragmentation of religious authority has given rise to a real phenomenon in the midst of society in the form of ideological political contestation played by two large mass organizations in Indonesia in determining the beginning of the qamariah month, NU and Muhammadiyah. The conception of power relations with the government is a problem that is often used as a basis for maintaining ideology and belief in a paradigm that has long been built. Moreover, religious issues drawn in ideological interests have led to a layer of group fanaticism which often makes religion a commodification of pragmatic interests.